Marie Antoinette, Princess of Versailles - Lasky, Kathryn (New York : Scholastic, 2000)
In 1769, thirteen-year-old Maria Antonia Josepha Johanna, daughter of Empress Maria Theresa, begins a journal chronicling her life at the Austrian court and her preparations for her future role as queen of France.
"Austria-France, 1769"--Cover.
School Library Journal
Books for the Teen Age (NYPL)
Booklist
6.7
5-8
Keywords: Marie Antoinette, -- Queen, consort of Louis XVI, King of France, -- 1755-1793 -- Childhood and youth -- Juvenile fiction; Marie Antoinette, -- Queen, consort of Louis XVI, King of France, -- 1755-1793 -- Childhood and youth -- Fiction; Kings, queens, rulers, etc. -- Fiction; Diaries -- Fiction; Marie Antoinette, -- Queen, consort of Louis XVI, King of France, -- 1755-1793 -- Fiction; Kings and rulers -- Fiction; Diaries -- Fiction